The use of video-modelling as a method for improving the social play skills of children with attention deficit hyperactivity disorder (ADHD) and their playmates - Wilkes-Gillan, S.; Cantrill, A.; Cordier, Reinie; Barnes, G.; Hancock, N.; Bundy, A. (The College of Occupational Therapists - UK, 2017)
Introduction: We investigated child outcomes and mothers' perspectives following technology-based intervention sessions aimed at improving children's social play skills. Method: Participants in this multiple case study included five children with attention deficit hyperactivity disorder, their mothers and five typically developing playmates, who had completed a parent-delivered play-based intervention 18 months previously. The initial intervention included the use of a technology-based interactive DVD at home and clinic-based sessions involving video-modelling. In this study, children received two additional technology-based clinic sessions involving video-modelling. Children's social play skills were measured pre- to post-intervention using the Test of Playfulness. Trends in scores were descriptively analysed by case. Mothers' perspectives were explored through semi-structured interviews; data were descriptively analysed by group and case. Results: Two children with attention deficit hyperactivity disorder showed an increase in their social play skills, and three a decrease in skills. Of the playmates, three showed consistent social play skills, one an increase and one a decrease. Qualitative findings suggest parents felt better able to support their child. Parents also suggested next steps for the intervention were necessary as their child continued to develop. Conclusion: Additional intervention support using technology after initial intervention may need to be adapted to different developmental stages and for use across different contexts.